The ability in pottery production of the pottery producer group of Ban Phakkhaya village, Atsaphone district, Savannakhet province: https://doi.org/10.69692/SUJMRD0802135 - BANMANIVONG, Lidsada; KHEMMARATH , Sitha; TOUNMANYSONE , Thongsa; MANIVONG, Vannasinh; VONGKEO, Somphone; LATSAVAT, Soulang; MONEPADITH , Soksay (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
study on the pottery production ability of the pottery producer group of Ban Phakkhaya village, Atsaphone district, Savannakhet province, with the objective: 1. Study on production process of the pottery producer group of Ban Phakkhaya village, Atsaphone district, Savannakhet province, 2. Study on the The ability in pottery production of the pottery producer group of Ban Phakkhaya village, Atsaphone district, Savannakhet province, the researchers use descriptive statistics to explain the process and ability of the samples with 3 heads of production group and collection data by open-ended questionnaire and observation. Findings from the study: There are 3 steps in the production process, such as the clay preparation process, the molding process, and the firing process. Equipment for production includes pin or hand wheel (phean), long-handled curved sword (ngao or hok), comb (Wi), a stick made from bamboo (Mai Tee Din), Krok or a square wooden (Mai Yieb Teen), design stick (Mai Lai), and string (Xerk). For the ability of pottery producers, each group made the same type and similar shape, using the same knowledge source from their ancestor, using only one kiln. The first group can produce 1.537 potteries, making revenue of about 18,720,000 kip per time. The second group can produce 1,675 potteries per time, making revenue of about 36,625,000 kip per time. The third group can produce 667 potteries, making revenue of about 10,180,000 kip per time. When calculated as the proportion per person in pottery production, the first group has the highest bility.